A review on analyzers for mass spectrometry - PRINCY AGARWAL,; ANJU GOYAL, (International Journal of Pharma and Bio Sciences, 2017)
Mass spectrometry is a technique used for measuring the molecular weight and determining the molecular formula of an organic compound. The complete process involves the conversion of the sample into gaseous ions, with or without fragmentation, which are then characterized by their mass to charge ratios (m/z) and relative abundances. The MS principle consists of ionizing chemical compounds to generate charge molecules or molecule fragments and measurement of their mass-to-charge ratio by using the one of a variety of techniques. A mass analyzer is an essential component of the mass spectrometer that after taking ionized masses separates them on the basis of charge to mass ratio and then outputs them to the detector where they are detected according to m/z ratio and converted to a digital output for an easy interpretation. The detector records either the charge induced or the current produced when an ion passes by or hits a surface and displays results in the form of spectrum. This article provides an overview of mass spectrometry, focusing on various types of analyzers used; principles of operation and current performance capabilities of mass analyzers and their significance in the development of mass spectrometry in molecular analysis, while briefly touching on ion detectors and the concept of vacuum in a mass spectrometer.